A SURVEY OF FOREIGN LANGUAGE NEEDS IN AAN TOURISM VILLAGE, KLUNGKUNG, BALI - Jokosaharjo, Sulistyoadi; Ratih Wijayanti, Anak Agung; Paramita, Ni Luh Komang Julyanti (Jurnal Manajemen Pelayanan Hotel, 2022)
This simple survey research aims to find out the interest of Aan villagers in learning foreign languages. Aan village is chosen because it just obtained the Tourism Village legalization based on the Klungkung Regent Regulation Number 8 Year 2021. One of the requirements of a Tourism Village is the ability to communicate with local and international tourists. The survey in form of a questionnaire consists of 8 questions in which it primarily aims to find out the most preferred and prioritized foreign languages which are needed in Aan, days to conduct the language training, and suggestions related to the conduct of the language training. There were 21 respondents who were involved in the tourism activity in Aan village. The survey results show that the most needed foreign language training is English, in which, the training can be carried out on Sunday and Saturday. Most of the respondents suggest that the training should be carried out in fun ways and not too tense. Keywords: Survey, Foreign Language Training, Tourism Village.